2019
DOI: 10.3390/antiox8090377
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Antiproliferative Properties of Cornus mas L. Fruit Juice

Abstract: Cornus mas L. (Cornelian cherry) is a flowering plant indigenous to Europe and parts of Asia, mostly studied for the antimicrobial activity of its juice. In this report, we investigated the composition and the in vitro antioxidant capacity of Cornus mas L. fruit juice from Greece, as well as its antiproliferative properties in vitro and in vivo. The fruits showed a high content of citric, malic, and succinic acid, in contrast to their juice, which had a low concentration of organic acids. The juice demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…This may explain the stronger cytotoxic effect of C. mas extract on Caco-2 cells. The anti-proliferative activity of extracts obtained from C. mas flowers, leaves, and fruits has been demonstrated in the literature [36][37][38][39][40], as well as the activity of A. melanocarpa leaves, fruits, and stems [41][42][43][44] against cancer cells. To our knowledge, there have been no previous studies on the cytotoxicity of C. superba extracts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may explain the stronger cytotoxic effect of C. mas extract on Caco-2 cells. The anti-proliferative activity of extracts obtained from C. mas flowers, leaves, and fruits has been demonstrated in the literature [36][37][38][39][40], as well as the activity of A. melanocarpa leaves, fruits, and stems [41][42][43][44] against cancer cells. To our knowledge, there have been no previous studies on the cytotoxicity of C. superba extracts.…”
Section: Discussionmentioning
confidence: 94%
“…The extract inhibited cells proliferation in SKOV3, MCF-7, PC-3, and A549 cells by 81.8%, 81.9%, 81.6%, and 79.3%, respectively. Tiptiri-Kourpeti et al [39] demonstrated the cytotoxic activity of C. mas fruit juice against four human cancer cell lines and one murine cell line: mammary adenocarcinoma MCF-7, hepatocellular carcinoma HepG2 and colon adenocarcinomas Caco2, HT-29, andmurine colon carcinoma CT26. Cell viability was reduced by 40-50% following incubation with the highest concentration of juice.…”
Section: Discussionmentioning
confidence: 99%
“…This fact probably justifies the traditional applications of cornelian cherry [ 2 , 8 ]. Recently, several in vitro and in vivo studies have confirmed antioxidant, anti-inflammatory, antidiabetic, hypolipidemic, anti-atherosclerotic, antimicrobial, and anticancer activity of the fruits [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cornelian cherry ( Cornus mas L.) is a flowering plant that belongs to Cornaceae family, with occurrence in Southern and Central Europe, as well as Western Asia. Cornelian cherry fruit is used for food, syrup and jam production, and in the fermented form, it is used to make alcoholic beverage [ 21 , 22 ]. It is rich in proteins, vitamins, antioxidants, mineral matters [ 23 , 24 , 25 ], polyphenols (e.g., anthocyanins, flavonoids, catechins and tannins) and other essential supplements [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cornelian cherry fruit is used for food, syrup and jam production, and in the fermented form, it is used to make alcoholic beverage [ 21 , 22 ]. It is rich in proteins, vitamins, antioxidants, mineral matters [ 23 , 24 , 25 ], polyphenols (e.g., anthocyanins, flavonoids, catechins and tannins) and other essential supplements [ 22 ]. All of these compounds have antioxidant, antimicrobial, hypolipidemic, hyperinsulinemic [ 26 ], anti-inflammatory and anticancer properties and also offer positive support to the nervous and cardiovascular systems [ 25 ].…”
Section: Introductionmentioning
confidence: 99%